The level of compliance in the use of drugs based on the antihypertensive and the patient's classification of hypertension: A cross-sectional study - Muslim, Zamharira; Saktia, Linice; Pudiarifanti, Nadia (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: The objective of antihypertensive therapy is to regulate blood pressure in accordance with the patient's condition. Patient adherence to medication is a significant factor affecting the efficacy of hypertension treatment. Regulated blood pressure is an indicator of the efficacy of antihypertensive treatment. Objective: This study seeks to assess the correlation between adherence to antihypertensive medication and patient characteristics, antihypertensive kinds, and hypertension categorization. Methods: This research employed a descriptive-analytical methodology with a cross-sectional design. The sample method employed was purposive sampling. Seventy-eight respondents participated in interviews utilizing a compliance questionnaire. Statistical analysis of the data was conducted utilizing the chi-square test method. Results: The study showed that most respondents had a high level of compliance (46.15%). Most respondents had blood pressure in the stage 2 hypertension category (46.15%). Based on the results of the correlation test between the level of compliance with the classification of hypertension obtained (p = 0.000). Conclusion: The level of compliance in undergoing therapy is related to the patient's gender and hypertension classification, but is not statistically related to the type of antihypertensive used.